2003
DOI: 10.1007/s00234-003-1080-3
|View full text |Cite
|
Sign up to set email alerts
|

The cerebrovascular response to traditional acupuncture after stroke

Abstract: Acupuncture is useful in treating the nausea and vomiting related to chemotherapy, adult postoperative surgery pain and postoperative dental pain. We obtained single-photon emission computed tomography (SPECT) brain perfusion images of six patients with middle cerebral artery occlusion obtained before and after acupuncture and compared the changes in regional cerebral blood flow (rCBF) to those in normal control. Images were obtained before and after acupuncture at six traditional acupoints (LI 4, 10, 11, 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 18 publications
1
61
0
3
Order By: Relevance
“…A brain imaging study that used single-photon emission computed tomography has shown that acupuncture increases activity in peri-infarct regions within the motor cortex of stroke patients [6]. In the present study, conjunction analysis demonstrated common regions that are activated during either acupuncture stimulation or hand grip task.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A brain imaging study that used single-photon emission computed tomography has shown that acupuncture increases activity in peri-infarct regions within the motor cortex of stroke patients [6]. In the present study, conjunction analysis demonstrated common regions that are activated during either acupuncture stimulation or hand grip task.…”
Section: Discussionsupporting
confidence: 56%
“…Acupuncture alters pain threshold via release of neurotransmitters and neuropeptides [5]. Acupuncture also induces changes in regional cerebral blood flow surrounding infarcts [6]. However, to date, no convincing scientific evidence from clinical trials has been published showing acupuncture to be effective as a therapy after stroke in enhancing functional improvement [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…fMRI study of brain activation may illustrate the functional substrate of the purported therapeutically beneficial effect of acupuncture in stroke rehabilitation and features of the neural mechanism of acupuncture. Lee et al (13) reported acupuncture-induced changes in regional cerebral blood flow (rCBF) after stroke, using single photon emission computed tomography (SPECT) perfusion imaging. Focally increased CBF was observed in all patients, especially in the hypoperfused zone surrounding the ischemic lesion, the ipsilateral or contralateral sensorimotor area, or both.…”
mentioning
confidence: 99%
“…Litscher and colleagues 32 reported that acupuncture may increase mean values of regional cerebral oxygen saturation and significantly increase mean blood flow velocity of the right middle cerebral artery. Lee and coworkers 33 investigated the correlation between acupuncture and neuroimaging using single-photon emission computed tomography in patients with stroke. The results of their study suggested that postacupuncture images showed multiple activation sites in the periphery of the ischemic area or in the hypoperfused zone in the affected vascular territory.…”
Section: Discussionmentioning
confidence: 99%